Developing the Critical Thinking Disposition Scale for Secondary School Students: a Validity and Reliability Study - Yildirim Doner, Seyhan; Demir, Sezgin (Dergipark Akad, 2022)
Critical thinking disposition; expresses individuals' orientation towards using skills within the scope of critical thinking, such as analysis, evaluation, interpretation, and discussion. This study aims to develop a valid and reliable Critical Thinking Disposition Scale for secondary school 5th, 6th, 7th, and 8th-grade students (9-14 years old). A different sample group has been selected for exploratory factor analysis, test-retest, and confirmatory factor analysis, each time using the simple random sampling method. Cronbach's Alpha value has been determined as.87, Spearman-Brown and Guttman split-half value as.81 in the reliability analysis performed on the obtained data, and it has been found that the scale was quite reliable. It has been found that the scale also had internal consistency in test-retest applications. The internal consistency coefficient of.75 indicates that the consistency of the scale is high as a result of the test-retest. As a result of the exploratory factor analysis, the scale's 21-item three-factor scale structure, which has a total variance value of 42.94%, has been confirmed by confirmatory factor analysis (X-2 = 345.18, sd = 184 RMSEA = .042, NFI = .97, NNFI = .98, CFI = .99., GFI = .88, AGFI = .85, SRMR = .059). The construct reliability of the scale has been calculated as 93, and it has been concluded that the scale was reliable enough. As a result of the research, it can be stated that a valid and reliable Likert-type scale with 21 items and three dimensions has been introduced to the literature.
Keywords: critical thinking disposition; secondary school students; scale; validity; reliability